Reversal of Fluoride Induced Teratogenicity in Xenopus laevis using Iodine and Thyroxine - Ronoh, C.; Osano, O.; Rono , M. (Africa Environmental Review Journal, 2022)
Fluoride is present naturally in the environment. However, human activities in the environment have increased the levels significantly. The effect of Fluoride exposure to Xenopus laevis embryo development was determined under Frog Embryo Teratogenesis Assay- Xenopus (FETAX). The endpoint of the study was mortality, whole body length and malformations which were recorded before and at 96 h. LC50 of Fluoride as per the FETAX test was 420.46 ppm and the EC50 was 452.802 ppm which indicated the TI of 0.93 therefore making Fluoride embryolethal. The study aimed to check on the ability of Thyroxine and Iodine to reverse the effects of F on the development of the tadpoles. There was a decrease in mortality but an increase in teratogenic impacts after treatment with Iodine and Thyroxine. The study found that the reversal of the Fluoride induced impacts on the tadpoles’ treatments by Iodine and Thyroxine treatments did not show a significant difference (p value .079) in response of the tadpoles for each of the treatment.